Climate law and developing countries : legal and policy challenges for the world economy - Richardson, Benjamin J. (Edward Elgar Publishing Ltd. CheltenhamGB, 2009)
Introduces the phenomenon of climate change and considers the problem of climate change law in the context of developing countries. Situates this text in the broader legal academic literature and summarises the main points of the chapters. Focuses on several themes climate justice; expanding the scope of the climate change legal regimes; the Clean Development Mechanism and Mitigation Strategies; and climate policy bridging the North and South.